Lectotypification of Cryptocarya anamalayana Gamble (Lauraceae) with a note on its fruits (Bangladesh Journal of Plant Taxonomy, 2018)
Not available.Bangladesh J. Plant Taxon. 25(1): 107-111, 2018 (June)